Studi Mekanisme Kinetik dengan Parametrik Camshaft pada Selubung Bangunan Adaptif - Sjarifudin, Firza Utama (Bina Nusantara University, 2012)
Adaptation is essential to manage the problem of climate change. In order to meet the challenge, this paper proposes an adaptive building envelope system that can optimize its configuration by responding environmental changes to achieve new levels of sustainable performance and energy efficiency. Most current adaptive building envelope uses kinetic techniques make its formation transformable. However, the use of kinetic components such as a large amount of interactive motorized system that requires electrical power may alsocause further decrease the building energy efficiency. This paper proposes a camshaft mechanism system for adaptive building envelope that uses less motors, controllers, and sensors. This system uses pre-programmed analysis data of daily solar radiation changes to parametrically drive the number of rotation phase and length of nose (Lobe Lift) that generates the shape of camshaft. The camshaft then controls the values of opening and closing of the building envelope components. The advantages of this system are less energy consumption, less maintenance and lower cost since it uses fewer motors, controllers and wiring. In conclusion, this paper has developed a prototypical tool that facilitates a new approach to energy-efficient kinetic buildings.